Genetic study of root, quality and yield characteristics for drought tolerance in advance generation of bread wheat - Mishra, D.K.; Shukla, R.S. (Annals of Agricultural Research, 2014)
Damage caused by temperature extremes and drought could be minimized or eliminated by framing strategy to develop thermo tolerance genotypes during early growth period. Thus it is essential to identify the potential genotypes for drought and heat tolerance of wheat. Fifty four genotypes of advance wheat lines developed under the project using drought and heat tolerance donor were planted in a randomized complete block design with three replications at seed breeding farm of Plant Breeding & Genetics, JNKVV, Jabalpur in rabi 2007-08 under rainfed condition. The observation of yield, yield contributing traits, root characteristics and stem thickness were recorded as per standard procedure. Significant variation due to genotypes for all the characters revealed that the genotypes for all the characters under study. In the present investigation, high heritability coupled with high genetic advance was exhibited for characters like dry gluten. It was observed that spike density, biological yield per plant, spike length, harvest index, root biomass, 1000 grain weight, wet gluten and protein contents were positively correlated with grain yield and also had positive direct effect and therefore these traits should be given due importance while practicing selection, aimed for improvement of grain yield. Comprehensive examination of result revealed that the advance generation wheat lines tested for suitability for drought tolerance viz. JWJ 13, JWJ 4, JWJ 27, JWJ 34 and JWJ 52 are found superior than the best check MP 3173. these lines have high grain yield, moderate root length and biomass and moderate to high stem thickness may be given due importance for selection of drought tolerance genotypes of wheat and can also be used as donor for development of drought resistant genotypes.